Correlation of Neutrophil and Lymphocyte Counts in Patient Infected with Coronavirus (Covid-19) - Nur Alina Hidayatur Rizki; Anik Handayati; Ellies Tunjung Sari Maulidiyanti (Health Notions, 2022)
Coronavirus Disease 2019 (Covid-19) causes hyper-inflammation and poor clinical conditions leading to high mortality in the world. Neutrophil and lymphocyte counts are used to describe disease severity in many clinical conditions including COVID-19. The purpose of this study was to determine the relationship between neutrophils and lymphocyte counts in patients infected with the coronavirus (Covid-19). The type of research used was cross-sectional. The sample in this study were patients infected with the Coronavirus (Covid-19) in a special isolation room who did a complete blood check at Brawijaya Hospital Surabaya. Types of data obtained from LIS (Laboratory Information System). The results of the study on the number of neutrophils in coronavirus (Covid-19) patients at Brawijaya Hospital showed an average neutrophil count of 5,174 cells/uL and an average lymphocyte count of 1,514 cells/uL. Data analysis showed that there was no correlation between the number of neutrophils and lymphocytes in patients infected with the Coronavirus (Covid-19) at Brawijaya Hospital Surabaya, possibly related to differences in immunity in each person. Keywords: coronavirus (Covid-19); neutrophils; lymphocytes